Find the function h(x) = f(x) + g(x) if f(x) = 4 x + 2 and g(x) = x - 4.

h(x) = 4x + x + 6
h(x) = 4x + 1 -2
h(x) = 4x + x - 2
h(x) = 4x - 4

Respuesta :

I hope this helps you
Ver imagen Аноним

Answer:  The correct option is (C) [tex]h(x)=4x+x-2.[/tex]

Step-by-step explanation:  We are given three functions f(x), g(x) and h(x) as follows :

[tex]f(x)=4x+2\\\\g(x)=x-4\\\\h(x)=f(x)+g(x).[/tex]

We are to find the value of h(x).

To find the value of the function h(x), we just need to add the values f the functions f(x) and g(x).

Therefore, we get

[tex]h(x)\\\\=f(x)+g(x)\\\\=4x+2+x-4\\\\=4x+x-2.[/tex]

Thus, [tex]h(x)=4x+x-2.[/tex]

Option (C) is CORRECT.

ACCESS MORE